2004
DOI: 10.1089/jwh.2004.13.799
|View full text |Cite
|
Sign up to set email alerts
|

Life Span and Repeated Violence against Women during Military Service: Effects on Health Status and Outpatient Utilization

Abstract: Repeated violence exposure is a relatively common experience among women in the military, and this has substantial implications for their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 36 publications
6
117
2
2
Order By: Relevance
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
“…2 Although the reasons for elevated risk among female Veterans remain unknown, some theorize that women's exposure to violence-prone environments, such as violent childhood homes and the military, may elevate women's risk for IPV. 6,7 IPV may be particularly common among women seeking care at Veterans Health Affairs (VHA) health-care facilities. 6,8,9 Studies have found lifetime reports of IPV as high as 74 % among women receiving medical or mental health care at a specialty VHA women's health clinic, 6 and reports of past-year IPV among 24 % of women under 50 years old at one large Midwestern facility.…”
mentioning
confidence: 99%
“…9,11 Similar findings have been observed for women veterans who use VHA care. 7,[12][13][14] Research has also shown that female survivors of military sexual assault often experience more distrust and blame directed at medical staff, depression/anxiety, and reduced willingness to seek further help at military/VHA health care settings compared to women who have sought treatment for sexual assault at civilian facilities. 15 However, few studies have addressed how the experience of military sexual assault affects perceptions of specific health care-related dimensions (e.g., perceptions of medical professionals, characteristics of the health care setting) that may influence women veterans' use and satisfaction with VHA care.…”
Section: 2mentioning
confidence: 99%
“…[14][15][16] ACEs are also associated with risk behaviors (sexual risk behavior, substance use), which may be maladaptive behavioral responses to early childhood trauma resulting in later poor adult health. 17,18 Because multiple traumatic experiences can have particularly deleterious impacts on health, [19][20][21] early-life traumas like ACEs are important to consider among populations with high risks of adulthood trauma. Previous research documents high rates of unique forms of adulthood trauma among women veterans, including combat exposure, military sexual trauma, and intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%